Combined Methodologies for Determining In Vitro Bioavailability of Drugs and Prediction of In Vivo Bioequivalence From Pharmaceutical Oral Formulations - De Simone, A.; Davani, L.; Montanari, S.; Tumiatti, V.; Avanessian, S.; Testi, F.; Andrisano, V. (Frontiers in Chemistry, 2021)
With the aim of developing an in vitro model for the bioavailability (BA) prediction of drugs, we focused on the study of levonorgestrel (LVN) released by 1.5 mg generic and brand-name tablets. The developed method consisted in combining a standard dissolution test with an optimized parallel artificial membrane permeability assay (PAMPA) to gain insights into both drug release and gastrointestinal absorption. Interestingly, the obtained results revealed that the tablet standard dissolution test, combined with an optimized PAMPA, highlighted a significant decrease in the release (15 ± 0.01 μg min−1 vs 30 ± 0.01 μg min−1) and absorption (19 ± 7 × 10–6 ± 7 cm/s Pe vs 41 ± 15 × 10–6 cm/s Pe) profiles of a generic LVN tablet when compared to the brand-name formulation, explaining unbalanced in vivo bioequivalence (BE). By using this new approach, we could determine the actual LVN drug concentration dissolved in the medium, which theoretically can permeate the gastrointestinal (GI) barrier. In fact, insoluble LVN/excipient aggregates were found in the dissolution media giving rise to non-superimposable dissolution profiles between generic and brand-name LVN tablets. Hence, the results obtained by combining the dissolution test and PAMPA method provided important insights confirming that the combined methods can be useful in revealing crucial issues in the prediction of in vivo BE of drugs.